2009
DOI: 10.5194/acp-9-8247-2009
|View full text |Cite
|
Sign up to set email alerts
|

Use of a mobile laboratory to evaluate changes in on-road air pollutants during the Beijing 2008 Summer Olympics

Abstract: Abstract. China implemented systematic air pollution control measures during the 2008 Beijing Summer Olympics and Paralympics to improve air quality. This study used a versatile mobile laboratory to conduct in situ monitoring of on-road air pollutants along Beijing's Fourth Ring Road on 31 selected days before, during, and after the Olympics air pollution control period. A suite of instruments with response times of less than 30 s was used to measure temporal and spatial variations in traffic-related air pollu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 43 publications
(50 reference statements)
8
117
0
Order By: Relevance
“…On the contrary, we suggest that an effort to solely control emissions of primary particles is unlikely to be effective. Since the formation of severe urban and regional haze in China is ultimately attributable to its rapidly growing economy, fast urbanization, and large population, leading to lower standards but higher rates for air pollutant emissions (41), regulatory measures by the Chinese government to reduce the PM 2.5 levels and to minimize its regional to global impacts (1-5) may have profound consequences on China or even the world economy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, we suggest that an effort to solely control emissions of primary particles is unlikely to be effective. Since the formation of severe urban and regional haze in China is ultimately attributable to its rapidly growing economy, fast urbanization, and large population, leading to lower standards but higher rates for air pollutant emissions (41), regulatory measures by the Chinese government to reduce the PM 2.5 levels and to minimize its regional to global impacts (1-5) may have profound consequences on China or even the world economy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our measurements of gaseous species provide additional evidence on the contribution of urban-scale photochemical production to the measured dominant secondary aerosol constituents, confirming small contribution from primary emissions and regional transport of PM 2.5 . It should be pointed out that the pollution sources in Beijing are characteristic of the typical urban environments in China, i.e., with high emissions of VOCs and NO x from local transportation and SO 2 from regional industrial sources (26,27,41,42). Also, large contributions of VOCs and NO x from local traffic and SO 2 from regional industrial sources to secondary aerosol production have been previously identified in other global megacity areas (31).…”
Section: Significancementioning
confidence: 99%
“…Roadside and vehicle tail pipe exhaust measurements must be linked to understand the spatial nature of UFPs, as well as differences in actual pollutant concentrations along roadways. Recent studies in various countries (China, Finland, Germany, Netherland, Switzerland, and United States) have developed mobile monitoring platforms using real-time instruments in attempts to estimate on-road air pollution concentrations together with spatial and temporal gradients of UFPs and related air pollutants (Bukowiecki et al, 2002a, b;Canagaratna et al, 2004;Kittelson et al, 2004a, b;Pirjola et al, 2004;Weijers et al, 2004;Schneider et al, 2008;Wang et al, 2009). Highways and arterial roads have been targeted for these measurements in both rural and urban areas.…”
Section: Introcutionmentioning
confidence: 99%
“…For instance, the first attempt took place during the Beijing 2008 Olympic Games (Guo et al, 2013). Drastic control actions were executed to cut down the emissions of atmospheric pollutants from motor vehicles, industries, and building construction activities (UNEP, 2009;M. Wang et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%